BRAIN IMAGING VS. COMPUTATIONAL IMAGING: INTEGRATING NEUROSCIENCE INTO THE DIGITIZATION OF EDUCATION - Euphrosyne EFTHIMIADOU (Universitaria Publishing House, Craiova, 2024)
The alliance between neuroscience and education promotes better analysis of the learning process and enriching teaching practices to make it more dynamic and effective. On the one hand, cognitive neuroscience is concerned with our behavior and eventually our memory as well as the acquisition of our knowledge and reflexes according to four factors (attention, active engagement, feedback, consolidation), which determine the speed and facility of learning (Dehaene, 2012). On the other hand, emotional neuroscience studies the interactions between the heart and reason, moving towards a new neurobiology of feeling and social behavior (Damasio, 2017). With the increasing digitization of the educational context in the postpandemic era, it would be essential to consider, on the one hand, to what extent the implementation of new communication and collaboration tools makes it possible to condition our perception and stimulate memorization. On the other hand, we can get a look at social cognition in online interactions without neglecting the influence exerted by technological tools not only on the way of thinking but also on our mental balance. Finally, it is important to take a look at the future of computational neuroscience and Artificial Intelligence such as the Chatbot Generative Pre-Trained Transformer (ChatGPT) and even the Cerebro project, an innovative method for imaging brain activity with a view to linking neuroscience (for understanding the brain) and concrete strategies (for helping to learn) (Brault Foisy L.-M., Masson S., 2022, https://doi.org/10.26034/cortica.2022.1956).